An analysis of recommendations on psychological well-being during open and distance learning (ODL): students’ viewpoints / Nurfarawahidah Badruesham … [et al.] - Badruesham, Nurfarawahidah; Hasan, Hazlin; Nikman, Khairunisa; Ismail, Mohd Ikhwan; Muhamad Arib, Nadhirah (Universiti Teknologi MARA, Perlis, 2023)
The COVID-19 pandemic that hit Malaysia prompted the administration of Universiti Teknologi MARA (UiTM) to switch all its classes to the Open and Distance Learning (ODL) mode, which commenced in April 2020. The shift in the teaching and learning mode elicited a variety of responses from students as they grappled with their mixed emotions of anguish and uneasiness pertaining to ODL. They displayed signs of mental anguish through several comments and status updates posted on social networking sites. Thus, to help ease the problems with students’ psychological well-being while utilising the ODL mode amidst the COVID-19 pandemic, the researchers felt inclined to place more emphasis on recommendations from the perspectives of UiTM students in urban, suburban, and rural localities. A total of 1,931 students from all UiTM campuses responded to the DASS-21 online survey, which assessed their levels of depression, anxiety, and stress during ODL. Using Microsoft Excel software, the collected data were analysed, and all comments and recommendations provided by the respondents were then coded, categorised into themes and sub-themes, and reviewed to ensure accuracy. From 569 recommendations provided by the respondents on their perspectives on handling depression, anxiety, and stress, three major themes were identified: social support (value of peer support, expert support, significant person support, family support, and administrative assistance), self-care (need for self-management of emotions, spiritual and recreational activities, and outdoor activities), and learning environment (students’ learning preferences and in-person instruction). The results underline how crucial social support, self-care, and a supportive learning environment are for managing DAS. The findings are hoped to assist educational institutions in comprehending the types of resources and assistance they can provide to help students adjust to online education, even after the pandemic period.